Iron-based molybdenum catalyst with flower-like structure as well as preparation method and application of iron-based molybdenum catalyst

By dispersing single atom Mo on the Fe(OH)3-f substrate material to form an iron-based molybdenum catalyst with a flower-like structure, the problem of low antibiotic removal efficiency in water bodies is solved, and efficient and stable catalytic degradation effect is achieved.

CN119425711APending Publication Date: 2025-02-14Hefei Comprehensive Science Center Environmental Research Institute
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411782189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove antibiotics in water bodies, especially tetracycline antibiotics, and traditional removal methods have problems such as low efficiency and by-product contamination.

Method used

Using a flower-like structure, the single-atom Fenton-like Fenton-like catalyst is used to disperse single-atom Mo on Fe(OH)3-f substrate material to form Mo-O bonds, providing rich active sites and improving catalytic performance. and degradation efficiency.

Benefits of technology

It realizes efficient removal of tetracycline antibiotics in water bodies, improves the efficiency and stability of the catalytic degradation reaction, and reduces the generation of by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425711A_ABST
    Figure CN119425711A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based molybdenum catalyst of a flower-like structure and a preparation method and application thereof.The preparation method comprises the steps that ferric salt and hexamethylenetetramine are added into a polyether solution to be evenly stirred, then ethylene glycol is added, stirring continues to be conducted, and then a mixed solution is obtained after standing and aging; carrying out hydrothermal reaction on the mixed solution to prepare a Fe (OH) 3-f substrate material with a flower-like structure; the preparation method comprises the following steps: preparing a Fe (OH) 3-f substrate material into a substrate solution, immediately dropwise adding a molybdenum salt solution, carrying out a stirring reaction to obtain a product, and carrying out suction filtration, cleaning and drying to obtain the flower-like structure iron-based molybdenum catalyst. The preparation method comprises the following steps: dispersing monatomic Mo on Fe (OH) 3-f, and self-assembling and folding to form a flower-like structure; wherein Mo-O bonds are formed, so that surface electron transfer is facilitated; the flower-like structure can provide abundant active sites; therefore, the catalytic performance and the degradation efficiency on organic pollutants are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and specifically relates to an iron-based molybdenum single-atom Fenton-like catalyst with a flower-like structure, and a preparation method and application thereof. Background Art

[0002] During the extensive use of antibiotics, most antibiotics are difficult to be metabolized in humans and animals and enter wastewater treatment plants (WWTPs) with excreta. However, due to the limitations of biological treatment processes, antibiotics cannot be completely removed and are discharged into the environment, resulting in their detection in aquatic environments such as lakes, surface water, and wastewater. More and more studies have shown that although the concentration of antibiotics in aquatic environments is only ng / L to μg / L, their biological toxicity is very high and they may produce synergistic toxicity with other pollutants (such as microplastics), thereby affecting aquatic ecosystems.

[0003] Antibiotics are secondary metabolites produced by microorganisms (actinomycetes, bacteria, fungi) or higher plants with resistance genes. Currently, antibiotics are obtained through natural or artificial synthesis, semi-synthesis, etc., and are widely used in the medical industry, agricultural breeding, animal husbandry, etc. due to their high antibacterial effect. Among them, tetracycline antibiotics (TCs) are a class of broad-spectrum antibiotics with the advantages of low price, simple use, few side effects and high antibacterial activity. According to the structure, they can be divided into tetracycline (TC), oxytetracycline (OTC), chlortetracycline (CTC) and polycycline (DC). However, TCs have a long half-life in aquatic environments (34-329h), and can cause bacteria to increase their resistance to antibiotics, destroy microbial ecological communities and aquatic ecosystems, and thus pose a potential hazard to human health and ecosystems. Therefore, it is particularly important to efficiently remove antibiotics from water bodies.

[0004] At present, the traditional methods of removing antibiotics include physical, chemical and biochemical methods. Among them, physical methods are mainly based on adsorption and membrane separation technology. This type of technology often uses physical adsorption to intercept pollutants on the surface of the material, but it does not achieve the effect of complete removal. However, the biochemical method is inefficient due to the long metabolic cycle of microorganisms, and it is difficult to efficiently degrade pollutants. The chemical method reacts more quickly with antibiotics in water and removes them more thoroughly, but it is easy to cause secondary pollution.

[0005] Advanced oxidation process is the use of superactivated oxidants (H 2 O 2 , persulfate, O 2 , O 3 etc.) to produce hydroxyl radicals (·OH), sulfate radicals (SO 4 ·- ), superoxide radicals (·O 2- ) and singlet oxygen ( 1 O 2 ) and other active oxygen species, gradually oxidizing the target pollutants into low-toxic or non-toxic small molecules until they are mineralized into H 2 O、CO 2 and inorganic ions. In recent years, sulfate radical-based advanced oxidation processes (SR-AOPs) have been widely studied by scholars due to their ability to efficiently degrade organic pollutants. 4 ·- Has a higher standard reduction potential (E 0 =2.5-3.1V), has a longer half-life in the environment (30-40μs), and can be produced in a wide pH range. In addition, it tends to react with pollutants during electron transfer. Therefore, SR-AOPs are considered to be the most promising technology for degrading organic pollutants. However, due to the late start of research on this technology, there are still many problems that need to be solved, such as: lack of understanding of catalyst selection and design; free radical and non-free radical transformation mechanisms, etc.

[0006] In recent years, single atom catalysts (SACs) have made great progress in environmental governance and are widely used in Fenton-like catalytic reactions based on peroxymonosulfate (PMS) to remove organic pollutants from water. Their advantages are: (1) simple preparation; (2) almost 100% atomic utilization; (3) abundant atomic active sites and unique electronic structure; (4) easy identification of catalytic mechanisms and active sites. Among them, molybdenum (Mo), as a common transition metal, has the characteristics of simple preparation, low price, low toxicity, and easy activation, making single atom Mo an ideal SR-AOPs catalyst. Among them, Mo reducing metal elements can effectively accelerate the transition metal-mediated PMS activation process, accelerate the electron migration rate on the material surface, increase the charge density, and significantly improve the catalytic efficiency. In addition, among many transition metal substrate materials, flower-like structures are widely used in energy catalysis, environmental remediation and other fields because of their advantages such as large specific surface area and abundant active sites. However, transition metal catalysts may have ion dissolution during the activation process, which in turn leads to secondary pollution of water bodies, and the actual use effect is not ideal. Summary of the invention

[0007] The purpose of the present invention is to provide a flower-like structured iron-based molybdenum single atom Fenton-like catalyst and its preparation method and application. 3 -f is used as the base material of single-atom Mo, and single-atom Mo is dispersed in Fe(OH) 3 -f, by forming a Mo-O bond, due to Fe(OH) 3-f has a flower-like structure that can provide abundant active sites, thereby increasing the number of active sites with catalytic activity for the reaction, thereby improving the catalytic performance and degradation efficiency of the composite material.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing an iron-based molybdenum catalyst with a flower-like structure comprises the following steps:

[0010] S1, adding iron salt and hexamethylenetetramine to the polyether solution and stirring evenly, then adding ethylene glycol and continuing stirring, and then standing for aging to obtain a mixed solution;

[0011] The molecular weight of the polyether is greater than 5000, such as polyether P123, which is used as a dispersant. The role of adding ethylene glycol is to assist the dispersant polyether in promoting the separation of the lamellar phase.

[0012] S2, subjecting the mixed solution to a hydrothermal reaction to obtain a flower-like structure of Fe(OH) 3 -f base material;

[0013] S3, Fe(OH) 3 -f After the base material is made into the base liquid, the molybdenum salt solution is immediately added dropwise, and the product is obtained by stirring and reacting. The product is filtered, washed and dried to obtain an iron-based molybdenum catalyst with a flower-like structure.

[0014] In a further embodiment, in step S1, the polyether solution is a clear solution obtained by adding a polyether with a molecular weight greater than 5000 to ethanol and dissolving it by ultrasonication; the concentration of the polyether solution is 2 to 25 mmol / L;

[0015] The iron salt is a trivalent iron salt, including iron nitrate, iron sulfate or iron chloride and hydrates thereof.

[0016] In a further embodiment, in step S1, the molar ratio of the iron salt, hexamethylenetetramine, polyether and ethylene glycol is 0.1-0.5:0.5-2:0.5-2:0.2-0.8.

[0017] In a further embodiment, in step S1, the aging time is 1 to 3 days;

[0018] In step S2, the temperature of the hydrothermal reaction is 150° C. to 170° C. and the time is 12 to 15 hours.

[0019] In a further embodiment, in step S3, the base liquid is Fe(OH) 3 -f The base material is added into anhydrous ethanol and dissolved by ultrasonic to obtain a solution with a concentration of 1 to 4 g / L;

[0020] The molybdenum salt solution is MoCl 5Or ammonium molybdate tetrahydrate is added to ethanol to form a molybdenum salt ethanol solution with a concentration of 2 to 4 g / L.

[0021] In a further embodiment, in step S3, the loading amount of Mo element in the iron-based molybdenum catalyst accounts for 10% of Fe(OH) 3 -f1 to 4% of the mass of the base material.

[0022] In a further scheme, in step S3, the filtration refers to filtration using a vacuum filter with a 0.22 μm organic phase filter membrane, the cleaning refers to alternating cleaning with deionized water and ethanol; and the drying refers to drying in a vacuum drying oven at 30 to 50° C. for 12 to 24 hours.

[0023] The second object of the present invention is to provide an iron-based molybdenum catalyst with a flower-like structure obtained by the above preparation method.

[0024] The third invention objective of the present invention is to provide the application of the above-mentioned flower-like structured iron-based molybdenum catalyst for removing organic pollutants in sewage.

[0025] A further solution is to remove organic pollutants from sewage by adding an iron-based molybdenum catalyst and peroxide to the sewage and stirring to perform a catalytic degradation reaction;

[0026] Wherein, based on the volume of sewage, the added amount of the iron-based molybdenum catalyst is 0.1-1 g / L, and the added amount of the peroxide is 0.1-0.5 g / L.

[0027] In a further embodiment, the organic pollutant includes at least one of tetracycline, oxytetracycline, chlortetracycline, doxycycline and their derivatives;

[0028] The peroxide is peroxymonosulfate (PMS), peroxydisulfate (PDS) or hydrogen peroxide (H 2 O 2 );

[0029] The stirring speed is 400-600 rpm, the temperature of the catalytic degradation reaction is 20-30° C., and the time is 30-60 min.

[0030] The beneficial effects of the present invention are:

[0031] The present invention first prepares Fe(OH) 3 -f is used as the base material, and its structure is self-assembled into a flower-like structure through high molecular weight polymer polyether as a dispersant; then high temperature polymerization and crystallization form transition metal-based hydroxides with atomic-level thickness. Since the self-assembled material is not restricted by the layered host material, a large amount of homogeneous nanomaterials can be formed, providing more dispersible empty sites for single atoms.

[0032] In addition, Fe(OH) 3 -f substrate material surface forms Mo-O covalent bonds with Mo single atom, and strong interactions between bonds are conducive to surface electron transfer and promote the decomposition of PMS. Therefore, the iron-based molybdenum catalyst (Mo@Fe(OH) 3 -f) is a Fenton-like catalyst that not only preserves Fe(OH) 3 -f base material has a flower-like structure, and the preparation method is simple to operate, the conditions are controllable, and it can be produced in large quantities.

[0033] Mo@Fe(OH) prepared by the present invention 3 -f type Fenton catalysts contain hydrophilic OH groups, which can improve the adsorption performance of organic pollutants such as oxytetracycline, reduce the mass transfer process during the reaction, and thus increase the degradation rate of oxytetracycline and other pollutants.

[0034] Mo@Fe(OH) prepared by the present invention 3 -f type Fenton catalyst, the introduction of stable low-valent Mo can form reaction sites with high catalytic activity, especially dispersed independent single atoms on transition metal-based materials, forming covalent chemical bonds with strong interactions, and enhancing the surface electron transfer rate. In this way, in the activation process of peroxide (permonosulfate (PMS)), the directional regulation of free radical pathways is achieved, and then the efficient removal of tetracycline antibiotics (oxytetracycline) pollutants is achieved.

[0035] Mo@Fe(OH) prepared by the present invention 3 The -f type Fenton catalyst has a thick flower-like structure. In addition, multiple Mo single-atom catalytic active sites are dispersed on the surface of the material. Utilizing these active sites, directed electron transfer occurs on the surface of the material, further improving the conversion rate of active oxygen species. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Mo@Fe(OH) prepared in Example 1 3 - SEM image of f;

[0037] Figure 2 Mo@Fe(OH) prepared in Example 1 3 -TEM image of f;

[0038] Figure 3 Mo@Fe(OH) prepared in Example 1 3 -f HADDF-SETM graph;

[0039] Figure 4 Fe(OH) prepared in Example 1 3 -f, Mo@Fe(OH) 3 -XRD pattern of f;

[0040] Figure 5 Mo@Fe(OH) prepared in Example 1 3 - FT-IR pattern of f;

[0041] Figure 6 Mo@Fe(OH) prepared in Example 1 3 -f XPS graph;

[0042] Figure 7 This is a diagram showing the degradation effects of different catalytic materials on oxytetracycline in water;

[0043] Figure 8 This is a graph showing the degradation effects of different catalytic materials on oxytetracycline in water under PMS conditions;

[0044] Fig. 9 This is a diagram of the quenching experiment on oxytetracycline degradation in water;

[0045] Fig.10 Mo@Fe(OH) prepared in Example 1 3 -f EPR diagram of oxytetracycline degradation catalyzed by peroxymonosulfate;

[0046] Fig.11 Mo@Fe(OH) prepared in Example 1 3 -f shows the degradation effect of oxytetracycline catalyzed by peroxymonosulfate in different water environments. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with several specific embodiments, but the essential content of the present invention is not limited to the following embodiments, and a person skilled in the art can and should know that any simple change or replacement based on the essence of the present invention falls within the scope of protection required by the present invention.

[0048] The molecular weight of the polyether in the following examples is greater than 5000; the other raw materials are all known products.

[0049] Embodiment 1:

[0050] 0.2 mmol of polyether was added to 30 mL of anhydrous ethanol, and a clear solution was formed by ultrasonic treatment; then 1 mmol of ferric nitrate nonahydrate and 1 mmol of hexamethylenetetramine were added, and the mixture was stirred evenly; then 0.5 mmol of ethylene glycol was added, and the mixture was stirred for a period of time, and then the mixture was allowed to stand for aging for 1 day to obtain a mixed solution;

[0051] The mixed solution was transferred to a high temperature and high pressure reactor for hydrothermal reaction at a temperature of 150°C for 15 hours. After the reaction, it was washed, centrifuged, and dried at 60°C overnight to obtain a flower-like structure of Fe(OH) 3-f base material;

[0052] Take 0.2g Fe(OH) 3 -f substrate material was added to 50 mL of anhydrous ethanol and ultrasonically oscillated to fully dissolve it to obtain a 4 g / L solution; then 5 mL of 4 g / L MoCl was quickly added dropwise 5 The ethanol solution was stirred evenly for several hours to achieve full contact, filtered through a vacuum filter with a 0.22 μm organic phase filter membrane, washed alternately with deionized water and ethanol, and finally vacuum dried at 40 ° C for 20 hours to obtain a wrinkled flower-like iron-based molybdenum catalyst (Mo@Fe(OH) 3 -f).

[0053] The loading amount of Mo in Fe-based molybdenum catalyst is 2.3477 W / m2 / cm2. 3 -f2.2% of the base material mass

[0054] Comparative Example 1:

[0055] Regular hexagonal sheet structure Mo@Fe(OH) 3 - Preparation of p:

[0056] 1.5 mmol of ferric chloride was dissolved in 30 mL of ethanol, and 2 mL of deionized water was added under magnetic stirring until it was completely dissolved, followed by the addition of 15 mmol of sodium acetate, and stirring was continued until it was fully dissolved.

[0057] The mixture was transferred to a high temperature and high pressure reactor and reacted at 180°C for 24 hours. After the reaction, the obtained solid was washed several times with deionized water and ethanol, and dried at 60°C overnight. The obtained α-Fe(OH) 3 -p.

[0058] Next, 1.0 mmol of ammonium molybdate tetrahydrate was dissolved in deionized water to form an aqueous solution, and 60 mg of α-Fe(OH) 3 -p, until the water evaporates, and then the sample is dried at 80 ° C for 12 h, and finally a regular hexagonal sheet structure Mo@Fe(OH) 3 -p.

[0059] Comparative Example 2:

[0060] The flower-like structure Mo@Fe(OH) synthesized in Example 1 3 -f was calcined in air, the reaction temperature was set to 350℃ and the time was set to 3h, and the obtained sample was Mo@Fe 3 O 4 .

[0061] Test example 1:

[0062] like Figure 1-6 They are respectively the flower-like structure Mo@Fe(OH) prepared in Example 1 3 -f catalyst SEM, TEM, HADDF-STEM, XRD, FT-IR and XPS patterns.

[0063] in Figure 1 , 2 The Mo@Fe(OH) prepared in Example 1 are 3 -f catalyst SEM and TEM images, both of which show that the prepared product Mo@Fe(OH) 3 The -f catalyst has a flower-like structure, showing a hydrotalcite-like structure, and its wrinkled flower-like structure has a good specific surface area and conductivity.

[0064] like Figure 3 The Mo@Fe(OH) prepared in Example 1 is shown. 3 -f catalyst HADDF-STEM image, the bright spots in the red circle represent Mo atoms. This shows that single Mo atoms are successfully dispersed in Fe(OH) 3 -f surface, and the single atomic Mo is evenly distributed without obvious agglomeration.

[0065] like Figure 4 The Fe(OH) prepared in Example 1 is shown. 3 -f, Mo@Fe(OH) 3 The XRD pattern of the -f catalyst shows that no characteristic peak of metal Mo oxide appears after dispersing Mo single atoms. Figure 5 Further analysis of the FT-IR spectrum of Mo@Fe(OH) 3 -f is the surface functional group of the catalyst, and its main absorption band is 3376cm -1 The stretching vibration peak of -OH is at 495 cm -1 A small absorption peak appears at the 3 -f Fe-O bonds of the base material.

[0066] like Figure 6 The XPS graph shown for Mo@Fe(OH) 3 -f is analyzed by analyzing the detailed chemical state of each element, Figure 6 a is the total spectrum, b, c, d are Mo 3d, Fe 2p and O1 s spectra respectively. There are two obvious peaks in the Mo 3d spectrum. According to previous literature, 232.2eV and 235.4eV correspond to Mo 6+ , 231.7eV and 234.9eV correspond to Mo 4+ , where Mo 6+ :Mo 4+The ratio is 1.40, indicating that Mo@Fe(OH) 3 The Mo in -f is mainly +6. In the Fe 2p spectrum, after anchoring the Mo single atom, Fe 3 + / Fe 2+ The ratio of Fe 3+ The content of Fe is reduced. In chemical synthesis, Fe obtains electrons and easily forms electron-rich centers, which plays an important role in the activation of PMS. In addition, when a single Mo atom is introduced into the substrate, O1s splits into three peaks, corresponding to adsorbed oxygen (531.8eV), Fe-O (530.6eV) and Mo-O (530eV), which further proves that Mo occupies the position of Fe and combines with O to form a Mo-O bond. Due to the strong interaction between the metal and oxygen bonds, Mo is better fixed on Fe(OH) 3 -f on the surface.

[0067] Test example 2:

[0068] The Mo@Fe(OH) prepared in Example 1 was used respectively. 3 -f, Fe(OH) 3 -f, Mo@Fe(OH) prepared in Comparative Examples 1 and 2 3 -p、Mo@Fe 3 O 4 , and their use in combination with PMS (Mo@Fe(OH) 3 -f+PMS, Fe(OH) 3 -f+PMS, Mo@Fe(OH) 3 -p+PMS、Mo@Fe 3 O 4 +PMS) was used as a degradation catalytic material in polluted water containing oxytetracycline, and its degradation effect on oxytetracycline was studied.

[0069] Experimental methods:

[0070] First, eight samples were prepared, each containing 20 ppm (recorded as the initial concentration C 0 ) 100 mL of oxytetracycline water sample was added with 10 mg of Mo@Fe(OH) 3 -f, Fe(OH) 3 -f, Mo@Fe(OH) 3 -p、Mo@Fe 3 O 4 ; 10 mg Mo@Fe(OH) was added to each of the last four water samples 3 -f+30mg PMS, 10mg Fe(OH) 3 -f+30mg PMS, Mo@Fe(OH)3 -p+30mg PMS, Mo@Fe 3 O 4 +30mg PMS;

[0071] Under the condition of 25℃, the mixture was dispersed by stirring at a speed of 500rpm, and the concentration of oxytetracycline in the water sample was detected by Agilent 1220 high performance liquid chromatography at time intervals of 0min, 2min, 5min, 10min, 20min, and 30min (recorded as the final concentration C). The results are as follows: Figure 7 , 8 As shown in the figure, the vertical axis represents the removal rate of oxytetracycline. The smaller the value, the greater the removal rate of oxytetracycline; conversely, the larger the value, the smaller the removal rate of oxytetracycline.

[0072] from Figure 7 It can be seen that the Mo@Fe(OH) prepared by the present invention 3 -f catalyst has the highest removal rate for oxytetracycline, that is, it has better adsorption performance; Figure 8 It can be seen that when Mo@Fe(OH) 3 When the -f catalyst works together with PMS, nearly 90% of oxytetracycline in water can be removed in 30 minutes. Compared with its flaky materials and oxide materials, its degradation performance is better.

[0073] Test example 3:

[0074] Same as in test example 2, add 10 mg Mo@Fe(OH) to 100 mL of water sample containing 20 ppm oxytetracycline. 3 -f and 30mg PMS were evenly dispersed as blank group; then different quenchers were added as control examples, and the oxytetracycline concentration in the water sample was detected by Agilent 1220 high performance liquid chromatography to calculate the degradation efficiency of oxytetracycline. Fig. 9 As shown in the figure, without adding any quencher, the degradation efficiency of oxytetracycline in the blank group can reach 90% within 30 minutes. When 1M tert-butyl alcohol is added, the degradation efficiency of oxytetracycline is reduced to 49%; when 1M methanol is added, the degradation efficiency of oxytetracycline is reduced to 44%. This shows that DMPO-·OH (hydroxyl radical) plays a major role in the degradation of oxytetracycline, and a small amount of DMPO-SO 4 ·- (sulfate free radical). However, when 1 mM L-histidine was added, the degradation efficiency of oxytetracycline remained basically unchanged, indicating that singlet oxygen 1 O 2 It has no effect on the degradation of oxytetracycline.

[0075] Fig.10 Mo@Fe(OH) prepared in Example 13 -f EPR diagram of the degradation of oxytetracycline by peroxymonosulfate (PMS) catalyzed by catalyst. 10mg Mo@Fe(OH) was added to 100mL of the water sample containing 20ppm oxytetracycline. 3 -f was evenly dispersed as the detection system, and then the free radical scavenger DMPO (100μL) was added to the detection system, and the resonance signal was detected by electron paramagnetic resonance (EPR) spectrometer. At this time, no signal was generated in the system; when 30mg PMS was added and reacted for 2min, a quartet with a signal intensity ratio of 1:2:2:1 was captured in the system, which was attributed to the characteristic peak of DMPO-·OH; as the reaction proceeded, the DMPO-·OH signal continued to increase, indicating that ·OH was continuously generated during the PMS activation process, which was consistent with the quenching experiment results. When the reaction was carried out for 10min, due to SO 4 ·- The signal is easily masked by the OH signal, and the weaker SO is detected. 4 ·- Signal.

[0076] As above, when the free radical scavenger TEMP (80 μL) was added to the detection system, Fig.10 As shown in the middle right figure, a strong 1:1:1 triplet peak was detected, which corresponds to the characteristic peak of TEMP oxidation product. This is because TEMP has a background value in aqueous solution, and the background needs to be subtracted in the actual measurement. When 30 mg PMS is added and reacted for 2-10 min, TEMP- 1 O 2 The signal intensity did not increase significantly, indicating that as the reaction proceeded, 1 O 2 It was not produced continuously, which is consistent with the results of quenching experiments.

[0077] Test example 4:

[0078] First, add oxytetracycline to 100 mL of pure water, tap water and reservoir water respectively to prepare contaminated water containing 20 ppm of oxytetracycline; then add 30 mg of PMS respectively, stir and react for 30 minutes to obtain three test water samples.

[0079] Weigh 20 mg of Mo@Fe(OH) prepared in Example 1 3 -f catalyst was added into the above three test water samples respectively, and the oxytetracycline concentration in the test water samples was detected by Agilent 1220 high performance liquid chromatography to calculate the degradation efficiency of oxytetracycline.

[0080] Fig.11 Mo@Fe(OH) was prepared for Example 1 3-f catalyst catalyzes the degradation of oxytetracycline by persulfate in different water environments. The results show that the degradation efficiency of oxytetracycline in different water environments is slightly different, roughly showing pure water (90%) > tap water (85%) > reservoir water (83%). This is mainly attributed to the fact that there are no impurities in pure water and the reaction conditions are optimal, while tap water has complex components and multiple anions coexist, resulting in a decrease in degradation efficiency, but basically maintaining a high degradation capacity, showing a relatively good ability to resist environmental interference.

[0081] Embodiment 2:

[0082] 0.1 mmol of polyether was added to 50 mL of anhydrous ethanol, and a clear solution was formed by ultrasonic treatment; then 0.5 mmol of ferric nitrate nonahydrate and 0.5 mmol of hexamethylenetetramine were added, and the mixture was stirred evenly; then 0.2 mmol of ethylene glycol was added, and the mixture was stirred for a period of time, and then the mixture was allowed to stand for aging for 2 days to obtain a mixed solution;

[0083] The mixed solution was transferred to a high temperature and high pressure reactor for hydrothermal reaction at 160°C for 13 hours. After the reaction, it was washed, centrifuged, and dried at 60°C overnight to obtain a flower-like structure of Fe(OH) 3 -f base material;

[0084] 0.1 g Fe(OH) 3 -f substrate material was added to 50 mL of anhydrous ethanol and ultrasonically oscillated to fully dissolve it to obtain a 2 g / L solution; then 10 mL of 2 g / L MoCl was quickly added dropwise 5 The ethanol solution was stirred evenly for several hours to achieve full contact, filtered through a vacuum filter with a 0.22 μm organic phase filter membrane, washed alternately with deionized water and ethanol, and finally vacuum dried at 30 ° C for 24 hours to obtain a wrinkled flower-like structure Mo@Fe(OH) 3 -f catalyst.

[0085] The loading amount of Mo in Fe-based molybdenum catalyst is 2.3477 W / m2 / cm2. 3 -f 3.5% of the mass of the substrate material.

[0086] Same as in Test Example 2, Mo@Fe(OH) prepared in Example 2 3 -f catalyst 20 mg was added to 100 mL of the water sample to be tested containing 20 ppm (recorded as the initial concentration) of chlortetracycline, and then 20 mg of peroxydisulfate was added; the catalytic degradation reaction was carried out at 30°C and 400 rpm with stirring for 60 minutes; the chlortetracycline concentration in the water sample to be tested (recorded as the final concentration) was detected by Agilent 1220 high performance liquid chromatography, and then the degradation effect was calculated.

[0087] After testing, the Mo@Fe(OH) prepared in Example 2 3 The degradation rate of chlortetracycline by -f catalyst was 85.6%.

[0088] Embodiment 3:

[0089] 0.5 mmol of polyether was added to 20 mL of anhydrous ethanol, and a clear solution was formed by ultrasonic treatment; then 2 mmol of ferric nitrate nonahydrate and 2 mmol of hexamethylenetetramine were added, and the mixture was stirred evenly; then 0.8 mmol of ethylene glycol was added, and the mixture was stirred for a period of time, and then the mixture was allowed to stand for aging for 3 days to obtain a mixed solution;

[0090] The mixed solution was transferred to a high temperature and high pressure reactor for hydrothermal reaction at 170°C for 12 hours. After the reaction, it was washed, centrifuged, and dried at 60°C overnight to obtain a flower-like structure of Fe(OH) 3 -f base material;

[0091] 0.05 g Fe(OH) 3 -f substrate material was added to 50 mL of anhydrous ethanol and ultrasonically oscillated to fully dissolve it to obtain a 1 g / L solution; then 8 mL of 3 g / L ammonium molybdate tetrahydrate ethanol solution was quickly added dropwise and stirred evenly for several hours to achieve full contact, and then filtered through a vacuum filter with a 0.22 μm organic phase filter membrane, and washed alternately with deionized water and ethanol, and finally vacuum dried at 50 ° C for 12 hours to obtain a wrinkled flower-like structure Mo@Fe(OH) 3 -f catalyst.

[0092] The loading amount of Mo in Fe-based molybdenum catalyst is 2.3477 W / m2 / cm2. 3 -f 1.6% of the mass of the substrate material.

[0093] As in Test Example 2, the Mo@Fe(OH) prepared in Example 3 was 3 -f catalyst 100 mg was added to 100 mL of the water sample to be tested containing 20 ppm (recorded as the initial concentration) of tetracycline, and then 30 mg of hydrogen peroxide was added; the catalytic degradation reaction was carried out at 30°C and 600 rpm with stirring for 50 minutes; the tetracycline concentration in the water sample to be tested (recorded as the final concentration) was detected by Agilent 1220 high performance liquid chromatography, and then the degradation effect was calculated.

[0094] After testing, the Mo@Fe(OH) prepared in Example 3 3 The degradation rate of tetracycline by -f catalyst was 95%.

[0095] Same as above, the amount of hydrogen peroxide added was adjusted to 50 mg; after testing, Mo@Fe(OH) 3 The degradation rate of tetracycline by -f catalyst reached nearly 100%.

[0096] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing an iron-based molybdenum catalyst with a flower-like structure, characterized in that: The steps include: S1, adding iron salt and hexamethylenetetramine to the polyether solution and stirring evenly, then adding ethylene glycol and continuing stirring, and then standing for aging to obtain a mixed solution; S2, subjecting the mixed solution to a hydrothermal reaction to obtain a Fe(OH)3-f substrate material with a flower-like structure; S3. After the Fe(OH)3-f base material is made into a base liquid, a molybdenum salt solution is immediately added dropwise, and the product is obtained by stirring the reaction. The product is filtered, washed, and dried to obtain an iron-based molybdenum catalyst with a flower-like structure.

2. The preparation method according to claim 1, characterized in that: In step S1, the polyether solution is a clear solution obtained by adding a polyether with a molecular weight greater than 5000 to ethanol and dissolving it by ultrasonication; the concentration of the polyether solution is 2-25 mmol / L; The iron salt is a trivalent iron salt; The molar ratio of polyether, hexamethylenetetramine, iron salt and ethylene glycol in the mixed solution is 0.1-0.5:0.5-2:0.5-2:0.2-0.

8.

3. The preparation method according to claim 1, characterized in that: In step S1, the aging time is 1 to 3 days; In step S2, the temperature of the hydrothermal reaction is 150° C. to 170° C. and the time is 12 to 15 hours.

4. The preparation method according to claim 1, characterized in that: In step S3, the base liquid is prepared by adding Fe(OH)3-f base material into anhydrous ethanol and dissolving by ultrasonication to obtain a solution with a concentration of 1 to 4 g / L; The molybdenum salt solution is prepared by adding MoCl5 or ammonium molybdate tetrahydrate into ethanol to form a molybdenum salt ethanol solution with a concentration of 2 to 4 g / L.

5. The preparation method according to claim 1, characterized in that: In step S3, the loading amount of the Mo element in the iron-based molybdenum catalyst accounts for 1 to 4% of the mass of the Fe(OH)3-f substrate material.

6. The preparation method according to claim 1, characterized in that: In step S3, the filtration refers to filtration using a vacuum filter with a 0.22 μm organic phase filter membrane, the cleaning refers to alternate cleaning with deionized water and ethanol, and the drying refers to drying in a vacuum drying oven at 30-50° C. for 12 to 24 hours.

7. An iron-based molybdenum catalyst with a flower-like structure obtained by the preparation method as described in any one of claims 1 to 6.

8. The use of the iron-based molybdenum catalyst with a flower-like structure as claimed in claim 7, characterized in that: It is used to remove organic pollutants from sewage.

9. The use according to claim 8, characterized in that: To remove organic pollutants from sewage, an iron-based molybdenum catalyst and peroxide are added to the sewage and stirred to perform a catalytic degradation reaction; Wherein, based on the volume of sewage, the added amount of the iron-based molybdenum catalyst is 0.1-1 g / L, and the added amount of the peroxide is 0.1-0.5 g / L.

10. The use according to claim 9, characterized in that: The organic pollutants include at least one of tetracycline, oxytetracycline, chlortetracycline, doxycycline and their derivatives; The peroxide is peroxymonosulfate, peroxydisulfate or hydrogen peroxide; The stirring speed is 400-600 rpm, the temperature of the catalytic degradation reaction is 20-30° C., and the time is 30-60 min.